Digital Transformation in Islamic Education Management Exploring the Vital Role of The UTAUT Model - Gumilang, Ahmad Naufal; Purnama, Sigit (EDUCAN : JURNAL PENDIDIKAN ISLAM, 2024)
This research discusses the role of the UTAUT Model (Unified Theory of Acceptance and Use of Technology) in Islamic education management. The main issue raised is how applying the UTAUT Model can influence and improve Islamic education management practices. This research aims to gain a better understanding of the factors that influence the acceptance and use of technology in the context of Islamic education management, as well as to guide the development of effective policies and programs. The research method used is qualitative with data collection through literature study. The analysis was carried out by identifying important findings in the literature related to the application of the UTAUT Model in Islamic education management. The results of this research indicate that the application of the UTAUT Model has significant potential to improve the quality of Islamic education through understanding the factors that influence technology adoption. However, there needs to be collaboration between Islamic education leaders, teachers, students, parents, and related stakeholders to encourage wider and sustainable technology adoption. In conclusion, a deep understanding of the role of the UTAUT Model in Islamic education management can make a significant contribution to improving the quality of Islamic education holistically.